Upaya Peningkatan Pemahaman Siswa Dalam Membedakan Pemanis Alami dan Pemanis Buatan pada Bahan Minuman Dengan Menggunakan Uji Semut di Kelas VIII.1 MTs 2 Kota Bima - Salmi Salmi (Lembaga Bale Literasi, 2022)
Theory in science subjects requires teachers to be active and creative inproviding real explanations to students. Statements, theories and opinions of experts must be proven empirically through scientific methods. One of them is material about additives in food. From there the author tries to lift it into a classroom action research conducted in two cycles. The data in this study was conducted using participant observation and written tests. Based on the results of the study it was concluded that the application of the experimental method using the help of ants could increase students' understanding in distinguishing natural sweeteners from artificial sweeteners in food. This is supported by the existence of research data which shows an increase in the percentage of completeness of written tests conducted in each cycle. The application of the experimental method using the help of ants is deemed appropriate to increase students' understanding of differentiating natural sweeteners from artificial sweeteners in Class VIII.1 MTsN 2 Kota Bima. The indicator of student understanding in cycle I obtained a final score of 75%, meaning that the indicator for improving student learning was in good criteria. In cycle II, the final score of students' comprehension indicators increased to 79% so that they are also in good criteria.